2019
DOI: 10.5455/javar.2019.f374
|View full text |Cite
|
Sign up to set email alerts
|

The effects of laser diode treatment on liver dysfunction of Mus musculus due to carbofuran exposure: An in vivo study

Abstract: Objective:The aim of this study is to determine the effect of laser diode as an alternative treatment on liver dysfunction (in vivo study) that is caused by carbofuran using male mice (Mus musculus) strain Balb/C.Materials and Methods:The samples were divided into three groups, namely, Group C–L– (control group, no treatment), Group C+L– (only treated by carbofuran treatment), and Group C+L+ (treatment group, treated by carbofuran and laser-puncture) with five replications each. After being treated, each liver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…Along with this, inflammatory cells aggregation was also seen in the perivascular area of central veins (Figure 1a, 1b). Up till now the most of the histopathological work related to CF intoxication is reported in Labeo rohita (Sarkar et al, 2005), African catfish (Hamed and Osman, 2017), Mus musculus (Astuti et al, 2019), and rats (Brkić et al, 2008), which showed the similar microscopic anomalies as elucidated in this study, however, there is no evidence of comparable findings in cattle egret in literature.…”
Section: Histopathological Examinationssupporting
confidence: 61%
“…Along with this, inflammatory cells aggregation was also seen in the perivascular area of central veins (Figure 1a, 1b). Up till now the most of the histopathological work related to CF intoxication is reported in Labeo rohita (Sarkar et al, 2005), African catfish (Hamed and Osman, 2017), Mus musculus (Astuti et al, 2019), and rats (Brkić et al, 2008), which showed the similar microscopic anomalies as elucidated in this study, however, there is no evidence of comparable findings in cattle egret in literature.…”
Section: Histopathological Examinationssupporting
confidence: 61%
“…One study points out that ST36 and LR3 may be effective in treating liver injury induced by carbon tetrachloride in rats [36]. Besides, one study showed that laser diode treatment applied to animal on Ganshu point (BL18) can repair live damage [37]. To prove the concept and investigate the effects of LA on hepatitis, regardless of vertical transmission or infection through needle use, we collected liver function data, including AST, ALT, and c-GT from participants.…”
Section: Discussionmentioning
confidence: 99%
“…Aside from having no adverse side effects, photobiomodulation therapy also has anti-inflammatory qualities [ 24 , 25 ]. Besides, other studies have shown that this therapy increases angiogenesis and stimulates muscle regeneration [ 26 ], liver dysfunction [ 27 ], brain [ 28 ], and peripheral nerve regeneration [ 29 ]. In order to treat both chronic pain and recent pain, photobiomodulation treatment has been widely employed in clinical practice and rehabilitation [ 30 ].…”
Section: Introductionmentioning
confidence: 99%